1997
DOI: 10.1136/adc.76.6.509
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support and growth in thalassaemia major

Abstract: Twelve thalassaemic children under 3 years of age received intensive nutritional support for one month and were discharged on a prescribed diet of locally available foods. Anthropometry, bioelectrical impedance analysis and dietary intake were longitudinally assessed. Mean energy intake was 20% greater than the recommended daily allowance during nutritional supplementation as compared with below the recommended daily allowance before and after the period of nutritional support. Weight, but not height, signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…Many early reports and interventional studies conducted outside the United States have shown that nutritional inadequacy may contribute to growth failure in some patients [35, 36]. In a recent TCRN study, 12% of pediatric, non-chronically transfused patients were underweight for height [37].…”
Section: Guidelines and Discussionmentioning
confidence: 99%
“…Many early reports and interventional studies conducted outside the United States have shown that nutritional inadequacy may contribute to growth failure in some patients [35, 36]. In a recent TCRN study, 12% of pediatric, non-chronically transfused patients were underweight for height [37].…”
Section: Guidelines and Discussionmentioning
confidence: 99%
“…Fuchs et al provided intensive nutrition support for one month in 12 young children (1 to 3 years) with Thal from Thailand and observed improvements in weight, height and body fat, which declined when nutrition support was removed [11,20]. Another group provided a high calorie diet to 15 children with Thal major from Egypt for 8 weeks [12].…”
Section: Discussionmentioning
confidence: 99%
“…The major side effect of multiple transfusions is iron overload leading to secondary hemochromatosis that affects multiple organs such as heart, liver, and endocrine glands and is responsible for deficits in bone mineral acquisition [38]. Various studies have shown that children with thalassemia major suffer from growth retardation, impaired immune function, and low body mass index [810]. The above treatment-related complications disrupt the balance between osteoblasts and osteoclasts by interfering with various molecular mechanisms leading to osteoporosis and increased fracture risk during adulthood [11, 12].…”
Section: Introductionmentioning
confidence: 99%